Strengthening ethics in the training of dental professionals from the perspective of personal bioethics - Vílchez Bellido, Dina (2018)
Training in ethics during university education is a necessity for the achievement of professionals committed to their work, so the development of strategies within an appropriate approach, which recognizes the ontological character of the person and his dignity, would allow its strengthening from the universities. The objective of this communication is to present the fundamentals that will later define the strategies for strengthening ethics in the training of professionals in dentistry, from the perspective of Personalist Bioethics. A descriptive-documentary research was developed, which included the analysis of the current problems of ethics in the training of professionals in dentistry, considering the revision of documents and curricular contents of four local universities; the theoretical bases of ethics in university training were presented and the perspective of Personalist Bioethics was explored. It is concluded that ethics should be developed considering strategies that contemplate a transversal presence of ethics throughout the curriculum, with a vision from the first person and within a non-relativist bioethics, such as that focused on personal bioethics, whose philosophical and anthropological bases allow consolidating the development of ethics during university education